Nordatlantisk antikatolisisme. Den amerikanske antikatolisismen fra 1776-1850 - Myhrer, Bendik Sundby (The University of Bergen, 2018)
Abstract The theme of this master thesis is North Atlantic anti-Catholicism with the reasearch question; Was the American anti-catholicism a unique form of anti-catholicism or just inherited from Britain? And did the increase in immigration during the 1820s, especially Irish Catholic, cause an increase in anti-catholic tendencies? Did this anti-catholicism differ from British and earlier forms of American anti-catholicism? To answer these questions, this thesis will start with a chapter about the protestant history of England, Great Britain and USA. It starts with Henry VIII and his break with the Catholic Church and follows with the tensions between parliament and the monarchy. The different laws that parliament passes that actively discriminates against the Catholic’s will mark the end of the chapter dedicated to England and Great Britain. The next part of the chapter is about USA and the difference in laws to England. The last part of the chapter is about the massive immigration during the 1820s and ending with the 1850s. The next chapter deal with how anti-catholicism appears in British research literature. The chapter is split into three parts, with the three parts looking at how Catholicism was perceived as a political, moral and social problem. The next two chapters covers the American anti-Catholicism during the years 1776-1850. This period is split, with one chapter dealing with the years 1776-1820 and the last chapter being about 1820-1850. 1776-1820 differs greatly from 1820-1850 and known for being an ecumenical period. This chapter explores how anti-Catholicism exists in a society where the laws state that every man is entitled to his own faith without interference from the government. The last chapter delves into the rampant anti-Catholicism following the increased number of Catholic immigrants to the US. This chapter is split into three parts, with Catholicism as a political, moral and social problem as its main sections. Historie mastergradsoppgave MAHF-HIS HIS350